2010
DOI: 10.1007/s00217-010-1333-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of some experimental variables and matrix components in the determination of antioxidant properties by β-carotene bleaching assay: experiments with BHT used as standard antioxidant

Abstract: The b-carotene bleaching assay belongs to the oldest and continuously commonly applied methods of estimating the antioxidant activity of compounds and mixtures. In this method, the antioxidant activity of the examined substance is evaluated by the spectrophotometric measurement of b-carotene concentration changes in bcarotene/peroxyl radicals (LOO • ) systems with and without antioxidant. Yet a little is known about factors influencing the value of inhibition percent of the investigated antioxidant, estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 25 publications
3
34
0
1
Order By: Relevance
“…The β-carotene bleaching assay in different versions has been applied in the assessment of various synthetic and natural antioxidant extracts. It was recently suggested that standardization of this method is necessary as the results can be significantly influenced by a number of factors, such as type and amount of solvent in which the antioxidants are dissolved, and presence of hydrogen and metal ions, among others (Dawidowicz & Olszowy, 2010).…”
Section: Measurement Of Antioxidant Activity In Model Emulsion Systemsmentioning
confidence: 99%
“…The β-carotene bleaching assay in different versions has been applied in the assessment of various synthetic and natural antioxidant extracts. It was recently suggested that standardization of this method is necessary as the results can be significantly influenced by a number of factors, such as type and amount of solvent in which the antioxidants are dissolved, and presence of hydrogen and metal ions, among others (Dawidowicz & Olszowy, 2010).…”
Section: Measurement Of Antioxidant Activity In Model Emulsion Systemsmentioning
confidence: 99%
“…Apart from their structural characteristics (number and position of -OH groups, inductive effects of other substituents present in the antioxidant molecule, steric hindrance/accessibility, packaging of an antioxidant around reactive species) the reactivity of an antioxidant depends significantly on reaction conditions such as solvent polarity, pH, temperature, type and concentration of reactive species. 3,[6][7][8][9][10][11][12][13][14] Since the selection of the method, the time and reaction conditions adopted to evaluate the content of antioxidants in a given sample significantly impact the determined values and, due to the fact that these parameters in a number of articles are relatively poorly described, it is very difficult to compare the results of AOP obtained for similar samples in different studies.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated [17] that the reaction kinetics between an antioxidant and peroxyl radicals in this method depends on the solvent type which account for the estimated antioxidant properties of the examined compounds. A question appears whether solvent type also influences the estimation of antioxidant properties of compounds by ABTS assay.…”
Section: Introductionmentioning
confidence: 99%